United against a common foe? The nature and origins of Euroscepticism among left-wing and right-wing citizens. Issue 6 (1st November 2016) - van Elsas, Erika J.; Hakhverdian, Armen; van der Brug, Wouter
Abstract: In Western European democracies opposition to the European Union is commonly found at the ideological extremes. Yet, the Euroscepticism of radical left-wing and radical right-wing parties has been shown to have distinct roots and manifestations. The article investigates whether these differences are mirrored at the citizen level. Using data from the European Election Study (2009/2014) and the European Social Survey (2008/2012) in 15 West European countries, it is found that left-wing and right-wing citizens not only differ in the object of their Euroscepticism, but also in their motivations for being sceptical of the EU. Left-wing Eurosceptics are dissatisfied with the current functioning of the EU, but do not oppose further European integration per se, while right-wing Eurosceptics categorically reject European integration. Euroscepticism among left-wing citizens is motivated by economic and cultural concerns, whereas for right-wing citizens Euroscepticism is solely anchored in cultural attitudes. These results refine the common 'horseshoe' understanding of ideology and Euroscepticism.